The creation of God - Pinxten, Rik (Gods, humans, and religions, 2010)
"This book develops a scientific approach to the phenomenon of religion. It is the conviction of the author that such an approach can only be comparative in nature, in order to overcome centuries of religiously-biased views on religion."--Publisher.